2007
DOI: 10.1364/oe.15.004359
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping of director structures and defects in liquid crystals using laser tweezers

Abstract: We demonstrate optical manipulation of structures and defects in liquid crystals (LCs). The effective refractive index depends on the LC molecular orientations and the laser beam's polarization. We use the orientation-mediated refractive index contrast for the laser trapping in LCs with a homogeneous composition, but with spatially-varying patterns of molecular orientations. Tightly-focused polarized beams allow for optical trapping of disclinations and their clusters, dislocations and oily streaks, cholesteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 44 publications
2
51
0
Order By: Relevance
“…It is noteworthy, that the laser trapping of bipolar dye-doped 7CB droplets using a circularly polarized light in heavy water caused their rotation as was earlier observed in the case of other nematic liquid crystal droplets [10,12,16,24]. In addition, complex visco-elastic flows and molecular reorientation patterns were observed in polariscope under circular and elliptical polarization of laser tweezers [25]; the complex molecular rotations are expected at such conditions [26,27].…”
Section: Molecular Orderingsupporting
confidence: 59%
“…It is noteworthy, that the laser trapping of bipolar dye-doped 7CB droplets using a circularly polarized light in heavy water caused their rotation as was earlier observed in the case of other nematic liquid crystal droplets [10,12,16,24]. In addition, complex visco-elastic flows and molecular reorientation patterns were observed in polariscope under circular and elliptical polarization of laser tweezers [25]; the complex molecular rotations are expected at such conditions [26,27].…”
Section: Molecular Orderingsupporting
confidence: 59%
“…The experimental sample fabrication techniques used throughout this study are highly reminiscent of those used in the multi-billion-dollar LC display industry, which can potentially stimulate the translation of our findings to the consumer markets. Previous studies have shown the ability to use specialty experimental systems involving micropatterned substrates [50], thickness gradients, and structured beams of light to control skyrmionic structures in equilibrium conditions [28,35,[50][51][52], however our work enables higher levels of dynamic control using low-intensity unstructured light. These advances add to the experimental toolkit available for controlling active behavior of solitons and promises new complex avenues and compelling possibilities for technological uses for LC skyrmions.…”
Section: Discussionmentioning
confidence: 99%
“…At laser powers of up to 30 mW, one can stretch the disclinations up to 10% for singular half-integer lines and up to about 5% for the nonsingular twistescaped defects. For the used parameters of the laser trap and material parameters of the system, we estimate that the maximum polarization-dependent force that can be exerted by the trap on a localized liquid crystal structure [36] is in the range 30-65 pN, depending upon the defect structure and laser polarization. From the balance of optical gradient force and defect line tension [36], we get T 1/2 ≈ 55-75 pN, and T 1 ≈ 95-115 pN, comparable to the line tensions of similar defects in the LC bulk [28,30] and consistent with the above estimates.…”
mentioning
confidence: 99%